The Learning Motivation of Tadris Science Students at UIN Imam Bonjol Padang on Online Learning - Raudhatul Jannah; Lufri Lufri; Andromeda Andromeda; Fatni Mufit; Sandijal Putra (STAI Miftahul Ula Nganjuk, 2022)
The research objective is to understand the learning motivation of Tadris IPA students at UIN Imam Bonjol Padang in online learning. The sample in the survey research is 36 students of Tadris IPA with data collection in the form of a motivational aspect questionnaire containing 10 statements via google form. Questionnaire analysis shows that the average aspect of motivation is 84% ??(very high motivation). It can be concluded that the Tadris IPA students of UIN Imam Bonjol Padang are very motivated to learn during online learning.